Harnessing Collaboration for Tourism in Kuta, Bali: Dual Analysing SWOT and Porters Diamond Model - I Made Chandra Mandira; I Gusti Ngurah Widya Hadi Saputra; Ni Putu Nina Eka Lestari; Anak Agung Ayu Ngurah Sri Rahayu Gorda; Anak Agung Ayu Ngurah Tini Rusmini Gorda; I Ketut Nuraga (Jurnal Ekonomi dan Studi Pembangunan, 2024)
The purpose of this study is to analyse and identify the factors of utilizing collaboration and exploring the strengths, weaknesses, opportunities, and threats of tourism in Kuta Beach, Bali, using a Penta helix approach that will be concluded using Porter's Diamond Model and the identification of collaborative strategies for tourism development. The research method uses a qualitative approach with RRA (rapid rural appraisal) techniques and SWOT analysis and uses Porter's Diamond Model in concluding, assisted by the N-Vivo Plus 12 application. The informants in this study totaled 16 people, with the criteria that 10 people were traditional leaders in Kuta Village, 2 were business people/MSMEs, 2 were academics, 2 were community members, 1 was a media person, and 1 was a government person, namely members of the people's representative council in Badung regency, Bali. The results of the research show that Penta helix collaboration plays a crucial role in the development of sustainable tourism. Real communication and collaboration with the same vision, namely realizing sustainable tourism by building cultural, social, economic, and environmental sustainability with crucial elements in the form of arts, health, accessibility, community, environment, and economic rotation